Evaluation of Technical Education and Training (Diklat) at the Human Resource Development Agency of East Java Province - Denok Elvira Hanindiya; Meirinawati M; Eva Hany Fanida; Fitrotun Niswah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Education and training are essential instruments in developing the competence and performance of civil servants. This study aims to analyze the evaluation of technical education and training programs at the Human Resource Development Agency (BPSDM) of East Java Province. The research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The evaluation of the training programs was analyzed using the Kirkpatrick evaluation model. The results indicate that technical training programs have been relatively effective at the reaction and learning levels, as evidenced by positive participant responses and improvements in knowledge and understanding of the training materials. However, effectiveness at the behavior and results levels has not been fully achieved. This condition is influenced by training planning that is not entirely based on participants’ needs, differences in initial competencies, limited practice time, and insufficient organizational support in encouraging the application of training outcomes in the workplace. This study concludes that improving training evaluation requires needs-based planning, more practical and applicable training design, and sustained organizational support to ensure that training outcomes lead to behavioral change and improved organizational performance at the Human Resource Development Agency of East Java Province.